Gut microbes improve prognosis of Klebsiella pneumoniae pulmonary infection through the lung-gut axis - Tang, Yuxiu; Chen, Liquan; Yang, Jin; Zhang, Suqing; Jin, Jun; Wei, Yao (Frontiers in Cellular and Infection Microbiology, 2024)
Background The gut microbiota plays a vital role in the development of sepsis and in protecting against pneumonia. Previous studies have demonstrated the existence of the gut-lung axis and the interaction between the gut and the lung, which is related to the prognosis of critically ill patients; however, most of these studies focused on chronic lung diseases and influenza virus infections. The purpose of this study was to investigate the effect of faecal microbiota transplantation (FMT) on Klebsiella pneumoniae-related pulmonary infection via the gut-lung axis and to compare the effects of FMT with those of traditional antibiotics to identify new therapeutic strategies. Methods We divided the mice into six groups: the blank control (PBS), pneumonia-derived sepsis (KP), pneumonia-derived sepsis + antibiotic (KP + PIP), pneumonia-derived sepsis + faecal microbiota transplantation(KP + FMT), antibiotic treatment control (KP+PIP+PBS), and pneumonia-derived sepsis+ antibiotic + faecal microbiota transplantation (KP + PIP + FMT) groups to compare the survival of mice, lung injury, inflammation response, airway barrier function and the intestinal flora, metabolites and drug resistance genes in each group. Results Alterations in specific intestinal flora can occur in the gut of patients with pneumonia-derived sepsis caused by Klebsiella pneumoniae. Compared with those in the faecal microbiota transplantation group, the antibiotic treatment group had lower levels of proinflammatory factors and higher levels of anti-inflammatory factors but less amelioration of lung pathology and improvement of airway epithelial barrier function. Additionally, the increase in opportunistic pathogens and drug resistance-related genes in the gut of mice was accompanied by decreased production of favourable fatty acids such as acetic acid, propionic acid, butyric acid, decanoic acid, and secondary bile acids such as chenodeoxycholic acid 3-sulfate, isodeoxycholic acid, taurodeoxycholic acid, and 3-dehydrocholic acid; the levels of these metabolites were restored by faecal microbiota transplantation. Faecal microbiota transplantation after antibiotic treatment can gradually ameliorate gut microbiota disorder caused by antibiotic treatment and reduce the number of drug resistance genes induced by antibiotics. Conclusion In contrast to direct antibiotic treatment, faecal microbiota transplantation improves the prognosis of mice with pneumonia-derived sepsis caused by Klebsiella pneumoniae by improving the structure of the intestinal flora and increasing the level of beneficial metabolites, fatty acids and secondary bile acids, thereby reducing systemic inflammation, repairing the barrier function of alveolar epithelial cells, and alleviating pathological damage to the lungs. The combination of antibiotics with faecal microbiota transplantation significantly alleviates intestinal microbiota disorder, reduces the selection for drug resistance genes caused by antibiotics, and mitigates lung lesions; these effects are superior to those following antibiotic monotherapy.